Efficacy of pancreatic enzyme replacement therapy in chronic pancreatitis: systematic review and meta-analysis - de la Iglesia-García, Daniel; Huang, Wei; Szatmary, Peter; Baston-Rey, Iria; Gonzalez-Lopez, Jaime; Prada-Ramallal, Guillermo; Mukherjee, Rajarshi; Nunes, Quentin M; Domínguez-Muñoz, J Enrique; Sutton, Robert (Gut, 2017)
ObjectiveThe benefits of pancreatic enzyme replacement therapy (PERT) in chronic pancreatitis (CP) are inadequately defined. We have undertaken a systematic review and meta-analysis of randomised controlled trials of PERT to determine the efficacy of PERT in exocrine pancreatic insufficiency (EPI) from CP.DesignMajor databases were searched from 1966 to 2015 inclusive. The primary outcome was coefficient of fat absorption (CFA). Effects of PERT versus baseline and versus placebo, and of different doses, formulations and schedules were determined.ResultsA total of 17 studies (511 patients with CP) were included and assessed qualitatively (Jadad score). Quantitative data were synthesised from 14 studies. PERT improved CFA compared with baseline (83.7±6.0 vs 63.1±15.0, p<0.00001; I2=89%) and placebo (83.2±5.5 vs 67.4±7.0, p=0.0001; I2=86%). PERT improved coefficient of nitrogen absorption, reduced faecal fat excretion, faecal nitrogen excretion, faecal weight and abdominal pain, without significant adverse events. Follow-up studies demonstrated that PERT increased serum nutritional parameters, improved GI symptoms and quality of life without significant adverse events. High-dose or enteric-coated enzymes showed a trend to greater effectiveness than low-dose or non-coated comparisons, respectively. Subgroup, sensitive and meta-regression analyses revealed that sample size, CP diagnostic criteria, study design and enzyme dose contributed to heterogeneity; data on health inequalities were lacking.ConclusionsPERT is indicated to correct EPI and malnutrition in CP and may be improved by higher doses, enteric coating, administration during food and acid suppression. Further studies are required to determine optimal regimens, the impact of health inequalities and long-term effects on nutrition.